Active Transient Acousto-Structural Response Control of a Smart Cavity-Coupled Circular Plate System - HASHEMINEJAD, Seyyed M.; SHAKERI, Rezgar (Archives of Acoustics, 2017)
The transient vibroacoustic response suppression of a piezo-coupled sandwich circular plate backed by a rigid-walled cylindrical acoustic enclosure is investigated. Problem formulation is based on the linear acoustic wave theory, Kirchhoff thin plate model, fluid/structure compatibility relations, Rayleigh integral formula, and active damping control (ADC) strategy. Matlab’s Genetic Algorithm (GA) is utilized to identify and optimize the feedback controller gain parameter based on a multi-objective performance index function. Durbin’s numerical Laplace inversion scheme is then used to calculate the key acousto-structural response parameters due to a transverse impulsive shock force for selected cavity depths. Numerical simulations demonstrate satisfactory performance of adopted control methodology in effective suppression of panel displacement response and radiated external sound pressure for enclosures of shallow and moderate depths. Limiting cases are considered and accuracy of the proposed model is rigorously verified.